Traumatised selves : does war trauma facilitate in-group bonding and out-group distancing? - Čorkalo Biruški, Dinka (Array, 2014)
This chapter discusses the role of communities in attributions of responsibility for the traumatising experience of war. A major challenge for post-war reconstruction is posed by the assignment of collective guilt to entire ethnic groups. The study presented in this chapter explores the level of traumatisation in two groups that were recently in conflict – the Croats and Serbs - their perception of collective guilt and their present inter-group relationships. On the basis of the existing literature, the authors expected to find a positive link between the level of traumatisation on the one hand and social distance towards the out group or nationalism on the other hand. The authors then wonder to what extent this relation is mediated by group-oriented processes, such as identification with one’s own ethnic group and group-based emotion of collective guilt assignment. Their findings show that the relationship is not as straightforward as one might have expected. War trauma appears to instigate a complex pattern of inter-group attitudes and emotions ; whereas it is directly related to negative out-group attitudes, trauma also influences the interpretation about the other group being responsible as a whole for the personal and collective hurt. Although there are somewhat different patterns of strength of selected mediators in Croatian and Serbian samples, findings about the importance of one specific group-based emotion - collective guilt assignment - is fairly firm and well grounded. The results show that this emotional response, either partially or completely, mediates the association between war-related traumatic experiences and (negative) out-group attitudes. Therefore, these results could have important implications for future intergroup relations of the antagonised groups and for the processes of social reconstruction.